Dimensi Kekerasan Terhadap Perempuan Batak Toba Dalam Praktik Budaya Paulakhon - Kristin Danayun Lumbantobing (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the dimensions of violence against Batak Toba women in the Paulakhon cultural practice. Patriarchal social structures embedded in Batak adat often perpetuate symbolic, structural, and physical violence against women, especially those failing reproductive roles, such as not bearing male offspring. Using a qualitative literature study approach, this research analyzes primary and secondary sources from 2021 to 2025, applying descriptive-analytical techniques with document review as the instrument and triangulation for validity. The population includes relevant literatures on Batak Toba culture and gender-based violence; purposive sampling selects the most pertinent studies. Results reveal multi-form violence in Paulakhon practices involving physical, verbal, and psychological abuse, underpinned by structural patriarchy that legitimizes discrimination and social stigma against women. The findings highlight the persistence of systemic violence embedded in cultural and social norms, negatively impacting women’s autonomy and family honor. The study concludes that Paulakhon represents a human rights violation reflecting entrenched patriarchal power structures, calling for culturally sensitive education and theological approaches to empower Batak Toba women and transform gender-biased traditions.